Diversity of Anaplasma and Ehrlichia/Neoehrlichia Agents in Terrestrial Wild Carnivores Worldwide: Implications for Human and Domestic Animal Health and Wildlife Conservation - André, Marcos Rogério (Frontiers in Veterinary Science, 2018)
In this review we aimed to review the genetic diversity of the tick-transmitted genera Ehrlichia, Anaplasma and ‘Candidatus Neoehrlichia sp.’ in wild carnivores Caniformia and Feliformia worldwide, discussing the implications for human and domestic animal health and wildlife conservation. Red foxes (Vulpes vulpes) have been identified as hosts for Anaplasma spp. (A. phagocytophilum, Anaplasma ovis, A. platys), Ehrlichia canis and ‘Candidatus Neoehrlichia sp.’ (FU98 strain) and may contribute to the maintaenance of A. phagocytophilum in Europe. Raccoons (Procyon lotor) have been reported as hosts for E. canis, A. bovis, ‘Candidatus Neoehrlichia lotoris’ and A. phagocytophilum, and play a role in the maintenance of A. phagocytophilum in the USA. Raccoon dogs (Nyctereutes procyonoides) may play a role as hosts for A. bovis and A. phagocytophilum. New Ehrlichia and/or Anaplasma genotypes circulate in wild canids and felids from South America and Africa. While Ehrlichia sp. closely related to E. canis has been reported in wild felids from Brazil and Japan, Anaplasma sp. closely related to A. phagocytophilum has been detected in wild felids from Brazil and Africa. Red foxes and mustelids (otters) are exposed to E. canis in countries located in the Mediaterranean basin, probably as a consequence of spillover from domestic dogs. Similarly, E. canis occurs in procyonids in North and South Hemispheres, in areas where E. canis is frequent in dogs. While ‘Candidatus Neoehrlichia lotoris’ seems to be a common and specific agent of raccoons in the USA, ‘Candidatus Neoehrlichia sp.’ (FU98 strain) seems to show a broader range of hosts, since it has been detected in red fox, golden jackal (Canis aureus) and badger (Meles meles) in Europe so far. Brown (Ursus arctos) and black (Ursus americanus) bears seem to play a role as hosts for A. phagocytophilum. Anaplasma bovis has been detected in wild Procyonidae, Canidae and Felidae in Asia and Brazil. In order to assess the real identity of the involved agents, future works should benefit from the application of MLST (Multi Locus Sequence Typing) aiming at shedding some light on the role of wild carnivores in the epidemiology of Anaplasmataceae agents.